DESIGN OF PV- CELLS AND MPPT BY USING ANFIS CONTROLLER - Madhavi, M; Reddy, G. VeeraShankara (International Journal of Computer Sciences and Engineering, 2018)
Solar photovoltaic technology is considered as one of the pure and clean technologies to produce electricity , but seems unattractive towards the use of it as a complement of electricity due to its low efficiency and high initial cost. As a result of its low efficiency it is nearly impossible to exploit the maximum solar power coming out of array therefore at its highest energy conversion output it leads to the operational failure of the device. As the radiation and temperature has their effects on the maximum power point, it is likely impossible to provide power operation at optimum level during all radiation levels. From years research are carried out on this and numerous MPPT techniques are introduced, refined , enforced and implemented with a proper execution. Different research groups have advocated different research methods which consist a little literature, where correlation between varieties of MPPT techniques are executed in terms of reliability, time of response and efficiency of conversion. This inspection gives a brief comparison among the realization of different MPPT methods and results a new MPPT technique with improve capability than the extant ones. The analysis done in this paper is as follows: At first, a solar PV array model based on MATLAB is first modeled and examined for validation following the employment of different techniques of MPPT under varying temperature on this PV array and different conditions for the effectiveness study of the particular MPPT technique.